AB0585 Clinical Characterization of Cutaneous Single-Organ Vasculitis According to Chapel Hill-2012 Criteria. Study of 60 Patients from A Series of 766 Cutaneous Vasculitis. (10th June 2014) - Loricera, J.; Blanco, R.; Pina, T.; Calvo-Río, V.; Ortiz-Sanjuán, F.; Santos-Gόmez, M.; Rueda-Gotor, J.; Άlvarez, L.; González-Vela, M.C.; González-Lόpez, M.A.; Armesto, S.; Marcellán, M.; et al.
Abstract : Background: Cutaneous vasculitis (CV) encompasses a wide group of entities characterized by skin blood vessels inflammation. Cutaneous single-organ vasculitis (CSOV) was recently defined according to Chapel Hill-2012 criteria as a CV limited to skin. To our knowledge, there is not any published report on CSOV. Objectives: Our aim was to characterize CSOV from a wide series of CV. Methods: We study CSOV from a series of 766 patients with CV from a single university center. CSOV was diagnosed according to Chapel Hill-2012 criteria. The following conditions were required: a) a skin biopsy showing characteristic leukocytoclastic vasculitis and b) vasculitis limited to skin. Results: We study 60 patients (26 women and 34 men) with a mean age ± SD of 55.70±16.25 years who fulfilled the Chapel Hill-2012 definition for CSOV. The main precipitating events were drug intake (26 patients, 52%) and a previous infection (17 patients, 34%). The main clinical manifestations were cutaneous (100%, palpable purpura in 81.7%) and fever (11 cases, 18.33%). The analytical findings were leukocytosis (mean; 13009±1082x10 9 /L) and elevated ESR (mean, 40.2±22.7 mm/1st hour). In most patients pharmacological therapies were not required (73.33%). In the remaining patients the drugs used were nonsteroidal anti-inflammatory drugs (13.3%), corticosteroids (15%), antihistaminic drugs (3.3%) and colchicine (1, 7%). After a median follow-up of 4 months [IQR:2-13] a complete recovery was observed in all the cases and relapses were observed in 5 (8.3%) patients. Conclusions: CSVO according to Chapel Hill-2012 criteria is a benign syndrome. Acknowledgements: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2706